2017
DOI: 10.1090/proc/13924
|View full text |Cite
|
Sign up to set email alerts
|

A criterion to generate carpet Julia sets

Abstract: Abstract. It was known that the Sierpiński carpets can appear as the Julia sets in the families of some rational maps. In this article we present a criterion that guarantees the existence of the carpet Julia sets in some rational maps having exactly one fixed (super-) attracting or parabolic basin. We show that this criterion can be applied to some well known rational maps, such as McMullen maps and Morosawa-Pilgrim family. Moreover, we give also some special examples whose Julia sets are Sierpiński carpets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…第一个 Sierpiński 地毯型 Julia 集是由 Milnor 和谭蕾 [513] 找到的. 更多的 Sierpiński 地毯型 Julia 集可参见文献 [240,246,316,570,762,771]. 对于这类特殊的 Julia 集, McMullen 提出了以下问题 (参见文献 [498, 问题 5.3]):…”
Section: 如果复球面上的一个紧子集内部为空 并可以写成可数多个球面直径趋向于零且闭包两两不交的unclassified
“…第一个 Sierpiński 地毯型 Julia 集是由 Milnor 和谭蕾 [513] 找到的. 更多的 Sierpiński 地毯型 Julia 集可参见文献 [240,246,316,570,762,771]. 对于这类特殊的 Julia 集, McMullen 提出了以下问题 (参见文献 [498, 问题 5.3]):…”
Section: 如果复球面上的一个紧子集内部为空 并可以写成可数多个球面直径趋向于零且闭包两两不交的unclassified
“…Further, it is found that the existence of polynomial semigroups such that the associated Julia set contains no interior points as well as Hausdorff dimension arbitrarily close to 2. A criterion studies in [61] for some rational maps having exactly one fixed (super-) attracting or parabolic basin that provides guarantee the existence of the carpet Julia sets.…”
Section: Different Approaches To Studying Dynamics Of One Variable Co...mentioning
confidence: 99%
“…As a kind of Julia sets, the Sierpiński carpets attract much interest recently. One may refer to [4], [2], [34], [11], [25] and the references therein.…”
Section: Some Dynamical Properties In the Non-quasicircle Casementioning
confidence: 99%